Inverse Lax-Wendroff Boundary Treatment: A Survey (Communications in Mathematical Research, 2022)
The inverse Lax-Wendroff (ILW) procedure is a numerical boundarytreatment technique, which allows finite difference schemes and other schemesto achieve stability and high order accuracy when using cartesian meshes tosolve boundary value problems defined on complex computational domain. Inthis short survey we summarize the main ingredients of the ILW procedure,discuss its applicability and stability properties, and provide possible directions of its future development.